Calvin, A Biography : a Biography. - Cottret, Bernard (Continuum International Pub. Group, 2003)
A major new authoritative and comprehensive biography, shedding new light on the life and personality of the great Reformer - and the milieu in which he lived and worked. CottretGÇÖs Calvin is not the GÇÿstaticGÇÖ theologian of earlier biographies, but a man of enormous vigour, constantly on the move in his thinking as well as in his life. Professor Cottret introduces the reader to the world into which Calvin was born, and follows him from childhood to humanistic and literary pursuits in Basel, to ministry in Geneva, to the halcyon Strasbourg years and finally back to Geneva. The vital issues.